Trans-intestinal cholesterol efflux is not mediated through high density lipoprotein - Vrins, Carlos L. J. (The American Society for Biochemistry and Molecular Biology, 2012)
Transintestinal cholesterol efflux (TICE) provides an attractive target to increase body cholesterol excretion. At present, the cholesterol donor responsible for direct delivery of plasma cholesterol to the intestine is unknown. In this study, we investigated the role of HDL in TICE. ATP-binding cassette protein A1 deficient (Abca1(−/−)) mice that lack HDL and wild-type (WT) mice were intravenously injected with chylomicron-like emulsion particles that contained radiolabeled cholesterol that is liberated in the liver and partly reenters the circulation. Both groups secreted radiolabeled cholesterol from plasma into intestinal lumen and TICE was unaltered between the two mouse models. To further investigate the role of HDL, we injected HDL with radiolabeled cholesterol in WT mice and Abca1(−/−)×Sr-b1(−/−) mice that lack HDL and are also unable to clear HDL via the liver. The intestines of both mice were unable to take up and secrete radiolabeled cholesterol from HDL via TICE. Although a generally accepted major player in the hepatobiliary route-based cholesterol excretion, HDL plays no significant role in TICE in mice.